EFFECT OF DIFFERENT DIETARY LEVELS OF FISH OIL ON COMMON CARP (Cyprinus carpio) GROWTH - Al - Obaidi,T. S. M.; Al – Bayaty,U. K.I.M (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate the impact of fish oil levels on the growth performance, feed efficiency, and body composition of common carp. The study divided 56 common carp into four treatment groups and fed diets containing different levels of fish oil over 56 days. Results showed significant differences in growth performance and feed efficiency between the treatments. The T3 (1.5% fish oil) and T4 (2% fish oil) groups showed the highest weight gain and most efficient feed conversion ratio, suggesting that 1.5% fish oil may support growth outcomes like those with 2% fish oil. Body composition analyses revealed favorable protein-to-fat ratios, suggesting improved nutrient retention and lean growth with reduced fish oil levels. These findings suggest that common carp can achieve satisfactory growth and feed efficiency with lower levels of fish oil, providing a more sustainable alternative to high-fish-oil diets.